Green synthesis of fish skeleton-like BaSO4 nanostructures by the ionic liquid designer template as nanofillers for supercapacitors application. (March 2022) - Dashti Najafi, M.; Kholghi Eshkalak, S.; Amiri, B.; Naderi, H.R.; Kowsari, E.; Chinnappan, A.; Ramakrishna, S.
Abstract: Recent developments in supercapacitors (SCs) have seen a remarkable increase in the electrochemical performance of the devices, which has led to the production of high-performance supercapacitors. In this study, we synthesized ceramic BaSO4 nanostructure with fish skeleton-like morphology through monocationic ionic liquid (IL-BaSO4 ) by a hydrothermal method. Herein, IL-BaSO4 blended with a conductive polymer, Poly ortho amino phenol (IL-BaSO4 /POAP), was used as an electrode in both three and two electrode systems. Synthesized material was characterized through Fourier transform infrared spectrometry (FT-IR), X-Ray Diffraction (XRD), and Scanning Electron Microscopy (SEM). For this purpose, IL-BaSO4 /POAP as the electrochemical functionality of the given electrodes was evaluated by cyclic voltammetry (CV), galvanostatic charge–discharge (GCD), and electrochemical impedance spectroscopy (EIS). The high specific capacitance of 624.3 F/g is obtained at a current density of 1 A/g for the IL-BaSO4 /POAP in the electrochemical measurement of three electrodes. A high energy and power density symmetric supercapacitor was also successfully designed using IL-BaSO4 /POAP as the anode and cathode electrodes in a 3 M KNO3 as the neutral electrolyte. The symmetrical supercapacitor (SSC) is capable of revolving in 0–1.3 V as a full potential window with a high energy density 35.4 W h/kg and power density of 650 W/kg for IL-BaSO4 /POAP//IL-BaSO4 /POAP. Besides, the SSC showed steady cycling ability for IL-BaSO4 /POAP//IL-BaSO4 /POAP retention capacity at 8 A/g following 3, 000 cycles, with 94.7%. Graphical abstract: Image 1 Highlights: The IL-BaSO4 with fish skeleton-like morphology is synthesized by using a hydrothermal method. The IL-BaSO4 /POAP electrode shows a specific capacitance of 624.3 F/g at 1 A/g in a three-electrode cell. Remarkable electrochemical behaviors for symmetrical supercapacitors.